Web-Based Umrah Administration Information System at PT. Nur Haramain Mulia Tour - Ahmad Risman; Riko Muhammad Suri; Muafi Muafi (Journal of Electrical Engineering and Computer (JEECOM), 2026)
PT. Nur Haramain Mulia Tour still handled several umrah administrative processes manually, including pilgrim registration, data retrieval, and report preparation. This condition reduced efficiency and increased the risk of data loss and service delays. This study aimed to develop a web-based umrah administration information system to improve administrative services, facilitate online registration, and support more structured data management. The system was developed using the Rapid Application Development approach, which consists of requirement planning, system design, and implementation stages. Data were collected through observation, interviews, and literature study, while the application was implemented using the Laravel framework and MySQL database. The resulting system supports major administrative functions, including registration, pilgrim data management, information access, and report generation within a centralized database environment. System evaluation was conducted using black-box testing for internal validation and questionnaire-based external testing involving administrative staff and prospective pilgrims. The external testing results showed a satisfaction score of 94%, indicating that the system was highly acceptable to users. The study concludes that the proposed web-based system improves the effectiveness and efficiency of umrah administrative services and assists both staff and pilgrims in managing registration and information processes more accurately and systematically.